PENGARUH PENDIDIKAN KEWIRAUSAHAAN, EFIKASI DIRI DAN DUKUNGAN KELUARGA TERHADAP NIAT BERWIRAUSAHA PADA MAHASISWA DI SURAKARTA - Karmelia, Mila; Ahsani, Riska Fii (Gapenas Publisher, 2025)
The research This research is survey research on students in the city of Surakarta, Central Java. The aim of this research is to examine the influence of entrepreneurship education, self-efficacy and family support on entrepreneurial intentions among students in Surakarta. The type of data used is quantitative data, the data source used is primary data. Data collection in this research was carried out by distributing researcher questionnaires to the respondents concerned. The population in this research are students in Surakarta who have received entrepreneurship education or are still active in entrepreneurship during the 2024/2025 lecture period. The sampling technique in this research used the Non Probability Sampling technique with Purposive Sampling and a sample of 96 respondents was obtained which was then rounded up to 100 respondents. Data was collected using a questionnaire that had been tested for validity and reliability. The data analysis technique uses multiple linear regression analysis, t test, F test, and coefficient of determination (R2). The results of this research indicate that entrepreneurship education does not have a significant effect on entrepreneurial intentions among students in Surakarta. Self-efficacy has a significant effect on entrepreneurial intentions among students in Surakarta. Family support has a significant effect on entrepreneurial intentions among students in Surakarta. The results of the coefficient of determination obtained an adjusted R square value of 0.592, which means that the contribution of the influence of the variables of entrepreneurship education, self-efficacy and family support to the entrepreneurial intention variable is 59.2%.